Efficacy and safety of TNF blockers and of ustekinumab in palmoplantar pustulosis and in acrodermatitis continua of Hallopeau. (30th March 2020) - Husson, B.; Barbe, C.; Hegazy, S.; Seneschal, J.; Aubin, F.; Mahé, E.; Jullien, D.; Sbidian, E.; D'Incan, M.; Conrad, C.; Brenaut, E.; Girard, C.; et al.
Abstract: Background: Palmoplantar pustulosis (PPP) and acrodermatitis continua of Hallopeau (ACH) are rare variants of psoriasis. Knowledge of the efficacy of biologics is scarce. Objectives: To evaluate the real‐life efficacy of tumour necrosis factor blockers and ustekinumab in PPP and in ACH. Methods: A multicentre retrospective descriptive study was conducted in 19 dermatology departments, including all patients with PPP or ACH seen from 2014 to 2016 who received one of the studied biologics. The data were collected by a standardized document. Factors associated with complete clearance (CC) were analysed by multivariate analysis, estimating odds ratios (ORs) and 95% confidence intervals (CIs). Results: Among 92 patients included, 50 received adalimumab, 44 ustekinumab, 36 etanercept and 31 infliximab. Improvement and CC were observed in 83.9% and 20.0% patients receiving infliximab, 75.0% and 38.6% ustekinumab, 57.1% and 20.0% etanercept and 60.4% and 29.2% adalimumab. We found no significant difference in CC rates or duration of treatment among the biological treatments ( P = 0.18 and P = 0.10, respectively). On multivariate analysis, CC with etanercept was associated with the ACH form and not smoking [OR = 9.5 (95% CI 1.1–82.7), P = 0.04 and 0.1 (0.01–0.9), P = 0.04]; with ustekinumab, male sex and absence of obesity [6.0 (1.3–28.6), P = 0.02 and 4.7 (1.0–22.7), P = 0.05]; with adalimumab, the ACH form [11.9 (2.7–52.3), P = 0.001]; and with infliximab, obesity [5.6 (1.1–29.4), P = 0.04]. Conclusions: We found no difference in efficacy between TNF blockers and ustekinumab and among the three different TNF blockers in real life for PPP or ACH, which reveals the heterogeneity of clinical response to biologics in pustular psoriasis as compared with plaque psoriasis.